2016
DOI: 10.1039/c6cy00902f
|View full text |Cite
|
Sign up to set email alerts
|

Activation of [CrCl3{PPh2N(iPr)PPh2}] for the selective oligomerisation of ethene: a Cr K-edge XAFS study

Abstract: The activation of the ethene tetramerisation catalyst system based upon [CrCl3(THF)3] and N( i Pr)(PPh2)2 has been investigated in situ via the reaction of [CrCl3{PPh2N(R)PPh2}(THF)] 1a (R= i Pr) with excess AlMe3 in toluene. The Cr K-edge XAFS spectrum of the solution freeze quenched after 1 min reaction time indicated monomethylation of the metal with the resultant product being [CrClMe(ClAlCl3){PPh2N(R)PPh2}(THF)] 4a (R= i Pr). After 5 minutes reaction time the XAFS spectra indicate that ~50% of 4a had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…The formation of dinuclear Cr(II) species like [Cr 2 Me 8 ] 4− was discussed by McGuinnes and co‐workers in a Cr−K‐edge XAFS study during the activation of [CrCl 3 {Ph 2 PN( i Pr)PPh 2 }] for the selective oligomerization of ethylene . The same group published DFT mechanistic studies on the ethylene tri‐ and tetramerization with Cr/PNP ligands regarding single versus double insertion pathways .…”
Section: Mechanistic Considerations Of Mono‐ and Dinuclear Species Tomentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of dinuclear Cr(II) species like [Cr 2 Me 8 ] 4− was discussed by McGuinnes and co‐workers in a Cr−K‐edge XAFS study during the activation of [CrCl 3 {Ph 2 PN( i Pr)PPh 2 }] for the selective oligomerization of ethylene . The same group published DFT mechanistic studies on the ethylene tri‐ and tetramerization with Cr/PNP ligands regarding single versus double insertion pathways .…”
Section: Mechanistic Considerations Of Mono‐ and Dinuclear Species Tomentioning
confidence: 99%
“…For this reason a comparison of different ligands regarding the formation of tri‐ and tetramers is meaningful. Very recently isotopic labelling and other experiments were reported concerning selectivity of 1‐hexene and 1‐octene formation in the ethylene oligomerization with the result that di‐ or multinuclear Cr species are not the active species in the mechanism . Nevertheless, there some results from substitution of sterically overcrowded PNPN−H and PNPNP ligands provide hints that large substituents lead to a shift from tri‐ to tetramerization.…”
Section: Introductionmentioning
confidence: 99%
“…In a freeze-quench XAS study, we observed the formation of ((C 6 H 5 ) 2 P) 2 N iPr CrMeCl in the reaction between ((C 6 H 5 ) 2 P) 2 N iPr )CrCl 3 (THF) and AlMe 3 . 14,15 In another study, Bercaw and coworkers performed an EPR and UV-vis study of a CrCl 3 complex containing the PNP ligand shown in Scheme 1a, functionalized with solubilizing groups. 16 Upon reaction of the complex with MMAO, a variety of Cr I , Cr III and EPR-silent complexes (dinuclear Cr I , or Cr II ) were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have developed a freeze‐quench XAS technique which allows for the trapping of reactive complexes . Freeze‐quench XAS is required to study these ethene trimerization systems due to catalyst deactivation occurring on the same timescale as a high‐quality EXAFS data acquisition times (several hours).…”
Section: Introductionmentioning
confidence: 99%
“…[12] Recently, we have developed a freeze-quench XAS technique which allows for the trapping of reactive complexes. [18][19][20] Freeze-quench XAS is required to study these ethene trimerization systems due to catalyst deactivation occurring on the same timescale as a high-quality EXAFS data acquisition times (several hours). The freeze-quench methodology allows for 'trapping' of reaction intermediates at different points in time, i. e. obtaining time-resolution, while freezing these intermediates allows long measurement times required for high quality data.…”
Section: Introductionmentioning
confidence: 99%